PROSPECTS FOR THYMUS PRESERVATION IN NEONATAL AND INFANT CHILDREN DURING CARDIAC SURGICAL TREATMENT OF CONGENITAL HEART DEFECTS (LITERATURE REVIEW) - Шабаев, Ильмир Фанилевич; Халивопуло, Иван Константинович; Ровда, Юрий Иванович; Ведерникова, Алена Владимировна; Шабалдин, Андрей Владимирович; Гришачева, Екатерина Олеговна; Шкитин, Ян Владимирович; Евтушенко, Алексей Валерьевич (Mother and Baby in Kuzbass, 2024)
Congenital heart defects are one of the most common forms of fetal malformations, along with pathologies of the central nervous system and gastrointestinal tract, which accounts for up to 47 % of all developmental defects [Krasuski R.A., Bashore T.M., 2016]. According to the AHA (American Heart Association), the birth rate of children with congenital heart disease is up to 1 %, of which about 25 % require surgical treatment during the first year of life [Mozaffarian D. etal., 2016]. In Russia, 0.7-1.7 % of children are born annually with heart defects, of which the vast majority require radical or palliative surgical correction during the first year of life. Moreover, critical defects are operated on during the neonatal period [Mutafyan O.A. et al., 2009]. Performing such early open surgery is sometimes extremely necessary to save the child’s life. At the same time, the inevitable removal of the thymus gland, as an important central organ of the immune system in the neonatal or infant periods of ontogenesis, may be critical for the subsequent formation of immune competence. Purpose of the study. To study possible and existing prospects for preserving the thymus in infants and young children during cardiac surgical treatment of congenital heart defects. Materials and methods. To search for sources of information, the following key words were used: thymectomy, immune status, congenital heart defects, immune response; radical surgical treatment, minimally invasive access to the heart - as well as their combinations. The main sites through which the search was carried out: https://scholar.google.ru and https://www.ncbi.nlm.nih.gov/pubmed. Results. The risk of developing immunodeficiencies after thymectomy in neonatal and infancy is still a matter of debate and debate. However, many years of research experience in this area every year more persistently demonstrates a direct relationship between the removal of the thymus gland during the period of its maximum activity in the postnatal period and the formation of disorders/depression of the immune system. Every year, new methods and proposals appear regarding the correction of the stages of surgical intervention - from significant ones, such as the use of minimally invasive methods, to the possible preservation of part of the thymus in order to enable the immune system to continue functioning. Options for minimally invasive approaches to the heart for cardiac surgical treatment of congenital heart defects with preservation of the thymus are presented. Conclusion: Due to the high relevance of the introduction of such organ-saving operations on the heart, insufficient information about their effectiveness, long-term consequences, and frequency of use in practice, the authors expect greater attention to be drawn to this problem by the scientific and practical community with wider discussion and exchange of experience.